Triaxial compression tests on bedding mortar samples looking at confinement effect analysis - Barbosa, C. S. (2007)
This paper presents an analysis of the mechanical behavior of bedding mortar samples under triaxial compression tests. When masonry is subjected to vertical loads, mechanical interactions between blocks and bedding mortar at the joints induce lateral tension and compression stresses. Thus, the mortar layer is submitted to a triaxial stress state that modifies its mechanical properties and behavior under confinement effects. This phenomenon may affect the failure mode of masonry and almost no information about this subject is found in literature. Here, test procedures are detailed and results are discussed. In addition to the compressive strength test results, also elastic modulus and Poisson ratio values are addressed. Significant differences were observed among triaxial and uniaxial standard test results. The obtained mortar behavior under different levels of lateral pressure is compared with test results done by other researchers in order to produce relevant conclusions for different mortar compositions.